1991
DOI: 10.1177/0887302x9100900402
|View full text |Cite
|
Sign up to set email alerts
|

Fashion Adoption: Theory and Pragmatics

Abstract: The Sproles'model of fashion adoption was selected to examine the adoption of the short skirt among employed women. Sproles'concepts of adopter identity and motivations were operationalized using measures from previous clothing-related studies of employed women. Results indicated that a large majority of the sample rejected the short skirt at the same time that retailers were heavily promoting the new style. Adopters and nonadopters differed significantly with respect to only two of the variables studied-age a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
3

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 11 publications
0
24
0
3
Order By: Relevance
“…Fashion adoption may be de®ned as aǹ individual decision-making process used for the adoption of any given style' (Forsythe et al 1991). Adoption models have been proposed by researchers either to explain or to predict the movement of new products through the consumer behaviour process.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Fashion adoption may be de®ned as aǹ individual decision-making process used for the adoption of any given style' (Forsythe et al 1991). Adoption models have been proposed by researchers either to explain or to predict the movement of new products through the consumer behaviour process.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Research has also shown that motivations that arise out of cognitive orientations towards dress, psychological identity, and social in¯uences, may have some impact on adopters' perceptions of a new apparel product (Forsythe et al 1991;Sproles and Burns 1994). Individuals differ in cognitive orientations and those differences in¯uence which products are adopted at a particular time (Sproles and Burns 1994).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…No consumo hedonista entende-se que o prazer em realizar uma compra cria uma associação positiva a esta atividade (Forsythe;Butler;Kim, 1991 Bettman (1973) propôs que cada classe de produto tem um risco associado a ela, sendo que tal risco passa a ficar saliente no momento em que o consumidor começa a interagir com a respectiva classe do bem. As percepções de risco (alta ou baixa) são reguladas por diferentes situações (Mcgregor, 2006).…”
Section: Aspectos Hedônicos E Utilitáriosunclassified
“…Esse valor é caracterizado pela materialização de desejos que resulta em um conjunto de sentimentos e emoções gerados pela experiência de consumo (Miller, 2000;Bardhi & Arnould, 2005). O prazer sentido ao consumir um produto ao qual se atribui valor hedônico cria uma associação positiva ao ato de consumir (Forsythe, Butler & Kim, 1991); por isso, os indivíduos que buscam a sensação proporcionada pelo consumo hedônico são mais consumistas (Scarpi, 2006).…”
Section: Produtos Como Símbolosunclassified